Puerarin Alleviates Vascular Cognitive Impairment in Vascular Dementia Rats - Zhu, Tiantian; Zhu, Moli; Qiu, Yue; Wu, Zeqing; Huang, Ning; Wan, Guangrui; Xu, Jian; Song, Ping; Wang, Shuangxi; Yin, Yaling; Li, Peng (Frontiers in Behavioral Neuroscience, 2021)
Cerebral ischemia triggers vascular dementia (VD), which is characterized by memory loss, cognitive deficits, and vascular injury in the brain. Puerarin (Pur) represents the major isoflavone glycoside of Radix Puerariae, with verified neuroprotective activity and cardiovascular protective effects. However, whether Pur ameliorates cognitive impairment and vascular injury in rats with permanent occlusion of bilateral common carotid arteries (BCCAO) remains unknown. This work aimed to assess Pur’s effects on BCCAO-induced VD and to dissect the underlying mechanisms, especially examining the function of transient receptor potential melastatin-related 2 (TRPM2) in alleviating cognitive deficits and vascular injuries. Rats with BCCAO developed VD. Pur (50, 100 and 150 mg/kg) dose-dependently attenuated the pathological changes, increased synaptic structural plasticity in the dorsal CA1 hippocampal region and decreased oxidative stress, which eventually reduced cognitive impairment and vascular injury in BCCAO rats. Notably, Pur-improved neuronal cell loss, synaptic structural plasticity and endothelial vasorelaxation function might be mediated by the ROS-dependent TRPM2/NMDAR pathway, evidenced by decreased levels of ROS, MDA, Bax, Bax/Bcl2 and TRPM2, and increased levels of SOD, Bcl2, and NR2A. In conclusion, Pur has therapeutic potential for VD, alleviating neuronal cell apoptosis and vascular injury, which may be related to the ROS-dependent TRPM2/NMDAR pathway.